IMPLEMENTASI KONSEP KEUNGGULAN TOM PETERS DALAM MENINGKATKAN DAYA SAING ORGANISASI PENDIDIKAN - Aulia, Fani; Sohiron, Sohiron (Jurnal Manajemen Pendidikan, 2026)
Increasingly fierce global competition demands educational organizations to transform and consistently improve quality excellence to maintain competitiveness. This study aims to analyze in depth how the concept of excellence, particularly based on Tom Peters' eight principles, can be implemented holistically to ensure the sustainable competitiveness of educational institutions. The approach used is a systematic literature study from various academic sources, including journals, books, and articles related to the concept of excellence, total quality management (TQM), and the competitiveness of educational organizations. The collected data were then analyzed by searching, grouping by theme, and synthesizing to obtain comprehensive conclusions. The findings indicate that to achieve sustainable competitiveness, educational organizations must implement eight principles: 1) Action orientation; 2) Closeness to customers (students and parents); 3) Autonomy and entrepreneurship; 4) Productivity through people (HR); 5) Practical and value-oriented culture; 6) Focus on core competencies; 7) Simple structure and lean staff; and 8) Simultaneous loose-tight approach. The conclusion of this study confirms that the competitiveness of educational organizations in the modern era is not solely determined by static factors, but rather by strategic consistency in instilling and implementing a culture of excellence across all institutional elements.